Pecularities of illness perception and health locus of control of alcohol addicts - Dirsienė, Jurgita; Zajančkauskaitė-Staskevičienė, Loreta (Psichologija, 2010)
Leventhal’s common sense model is a popular model for studying responses to health threats. The central prediction of the model is that coping responses are determined by an interrelated set of beliefs known as illness perceptions, which appear to be directly related to patient’s receptivity to the treatment and outcomes of the illness. The examination of how individuals perceive alcohol addiction may be important in prevention and may help health-care professionals individualize treatment strategies, thereby improving illness outcomes. The goal of the research was to determine the pecularities of and correlations between illness perception and health locus of control of alcohol-addicted people. The object and methods of research: 70 individuals with the diagnosis of alcohol addiction, currently going through alcohol detoxification in an addiction centre (49 men and 21 women). They completed the Brief Illness Perception Questionnaire (Broadbent et al., 2006) and Multidimensional Health Locus of Control Scale (MHLC; Wallston et al., 1978). Results of the study: Illness perception and health locus of control was not related to age, sex and education. The research showed that the participants who had a spouse had a more powerful others’ health control orientation than those who hadn’t (U = 419.5; p < 0.05). The research showed a statistically significant correlation between powerful others’ health control orientation and a shorter addiction duration (r = –0.249; p < 0.05). The longer addiction duration was positively related to the illness recognition (r = 0.481; p < 0.001) and the perception of a longer illness duration (r = 0.353; p < 0.05). The longest abstinence period was positively related to a better illness recognition (r = 0.270; p < 0.05) and the perception of a longer illness duration (r = 0.457; p < 0.05) and more severe illness consequences (r = 0.323; p < 0.05). Statistical analysis showed a lot of statistically significant correlations betveen illness perception dimensions: more negative consequences and a stronger illness identity were related to more concern about the illness and more negative emotions. The perception of illness coherence and a shorter duration of the illness was related to a better perceived personal control over the illnesss. The stronger concern about the illness was related to a better treatment control perception. The better illness recognition was related to the perception of longer illness duration, less personal control over the illness and more concern about the illness. The strength of the symptoms was positively related to a better illness coherence perception. The research showed a significant correlation between illness perception and health locus of control only for men: the internal health locus of control was related to the perception of a shorter illness duration (r = –0.402; p < 0.01) and less concern about the illness (r = –0.285; p < 0.05). The powerful others’ health control orientation was related to the perception of better treatment (r = 0.341; p < = 0,05) and personal control (r = 0.332; p < 0.05), more severe symptoms of illness (r = 0.032; p < 0.05), more concern (r = 0.404; p < 0.01) and negative emotions (r = 0.310; p < 0.05). Statistical analysis showed that alcoholics had an internal health control orientation. Illness recognition was associated with negative alcohol-related consequences, but not with the strength of symptoms. The implications and limitations of the findings, the implications for practice and research are discussed.